2022
DOI: 10.1021/acsomega.1c06029
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical [4 + 1] Tandem sp3(C–H) Double Amination for the Direct Synthesis of 3-Acyl-Functionalized Imidazo[1,5-a]pyridines

Abstract: 3-Acyl imidazo[1,5-a]pyridines, featured pharmaceutical moieties that were prepared by a three-step reaction conventionally, could be obtained in one step by an electrochemical tandem sp 3 (C−H) double amination of acetophenones with pyridine ethylamines using ammonium iodide as a redox mediator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…43 From 2018 to 2022, electrochemically promoted cyclization cascade reaction was also applied to the synthesis of imidazo[1,5-a]pyridines and imidazoles (Scheme 16). [44][45][46][47][48][49][50][51] The intramolecular electrochemical (3+2) cyclization reactions of pyridylamines with tethered internal alkynes of substrates 65 catalyzed by 66 in the presence of NaHCO3 and Et4NBF4 generated imidazo[1,5-a]pyridines 67 in up to 96% yields. 44,45 Electrochemically promoted the C-N formation/cyclization reactions between ketones (68 or 71) and pyridylamines (69 or 72) using HI or NH4I as the redox mediator to produce imidazo[1,5-a]pyridines 70 or 73 in moderate to excellent yields (70: 20-99%, 73: 31-90%).…”
Section: Synthesis Of Imidazo[15-a]pyridines and Imidazolesmentioning
confidence: 99%
See 3 more Smart Citations
“…43 From 2018 to 2022, electrochemically promoted cyclization cascade reaction was also applied to the synthesis of imidazo[1,5-a]pyridines and imidazoles (Scheme 16). [44][45][46][47][48][49][50][51] The intramolecular electrochemical (3+2) cyclization reactions of pyridylamines with tethered internal alkynes of substrates 65 catalyzed by 66 in the presence of NaHCO3 and Et4NBF4 generated imidazo[1,5-a]pyridines 67 in up to 96% yields. 44,45 Electrochemically promoted the C-N formation/cyclization reactions between ketones (68 or 71) and pyridylamines (69 or 72) using HI or NH4I as the redox mediator to produce imidazo[1,5-a]pyridines 70 or 73 in moderate to excellent yields (70: 20-99%, 73: 31-90%).…”
Section: Synthesis Of Imidazo[15-a]pyridines and Imidazolesmentioning
confidence: 99%
“…44,45 Electrochemically promoted the C-N formation/cyclization reactions between ketones (68 or 71) and pyridylamines (69 or 72) using HI or NH4I as the redox mediator to produce imidazo[1,5-a]pyridines 70 or 73 in moderate to excellent yields (70: 20-99%, 73: 31-90%). 46,47 Up to 99% yields of 1,3-disubstituted imidazo[1,5-a]quinolines 77 were obtained via an NH4I-mediated tandem electrocyclizations of quinolines (or pyridines) 74 with amines 75 or amino acids 76 in an undivided cell at a constant current density of 15 mA/cm 2 . 48 Interestingly, when both the reactants ketones 78 and amines 79 did not contain pyridine ring, the similar reaction system provided up to 95% or 62-81% yields of imidazoles 80.…”
Section: Synthesis Of Imidazo[15-a]pyridines and Imidazolesmentioning
confidence: 99%
See 2 more Smart Citations
“…imidazo­[1,5- a ]­pyridines, a class of carbonyl functionalized imidazo­[1,5- a ]­pyridines at the 3-position, have been extensively employed as a pharmacophore in many bioactive compounds. For example, 3-acyl imidazo­[1,5- a ]­pyridines are cannabinoid receptor type 2 (CB2) agonists that could be used to treat inflammatory pain and monosodium iodoacetate (MIA) osteoarthritis pain, and 3-amides imidazo­[1,5- a ]­pyridines are phosphatidylinositol 3-kinase (PI3K) inhibitors that could be used for related diseases. , However, synthesis of these skeletons by conventional methods were achieved through multistep reactions, and in the synthesis process the usage of highly corrosive reagent trichlorophosphate is inevitable and the yield of the cyclization step is unsatisfactory. The authors have reported an electrochemical method for one-step synthesis of 3-acyl imidazo­[1,5- a ]­pyridines via a sp 3 (C–H) functionalization, while direct functionalization of challenging inactive α- sp 3 (C–H) on esters and amide failed in our diversified investigation. Given this, development of an alternatively efficient method for direct introduction of esters and amides at the 3-position of imidazo­[1,5- a ]­pyridines from simple starting materials is of great significance.…”
mentioning
confidence: 99%